A precise radiation boundary method for dynamic response of a double-layered tunnel embedded in a layered half-space - Li, Zhi-yuan; Li, Jian-bo; Lin, Gao (Journal of applied geophysics, 2019)
In the study, a precise radiation boundary method (PRBM) is proposed to analyze the diffraction of elastic wave and dynamic stress concentration of a double-layered lining tunnel with a shock-absorbing layer embedded in a layered half-space. The dynamic response of the complex structure is obtained by using a substructure replacement technique, which transforms the complex scattering problem into a simple radiation one. The proposed method is applied to model the radiation condition of a boundary of a complex structure truncated from a multi-layered half-space in frequency domain. The proposed method is based on the precise integration algorithm which ensues the low computational effort and high accuracy. The accuracy and effectiveness of the proposed method are validated by comparing it with the results of extant studies. Finally, a comprehensive parametric study is conducted to investigate the effects of the complex geological structure (impedance ratio of layered soil and soft layer on surface) and complex constructions (double-layered lining and shock-absorbing layer) on the dynamic stress concentration of a composite-structure tunnel. The proposed approach exhibits a significant ability to analyze the response of a complex underground structure embedded in a layered half-space. •The PRBM satisfy the radiation condition and reduce the unknown variables.•Low computational efforts and the high accuracy of Green function in the layered half-space.•For arbitrarily irregular complex structures, no special treatment is needed.•A comprehensive set of results are shown to light on the dynamic response of the double-layer.